DETERMINANTS OF TAXPAYER COMPLIANCE WITH TAXATION SOCIALIZATION AS A MODERATION VARIABLE: (Case Study at KPP Pratama Tampan Pekanbaru) - Franciska Cindy Yulianty; Muhammad Ahyaruddin; Rama Gita Suci (Jurnal Akuntansi AKTIVA, 2023)
The purpose of this study was to analyze the effect of implementing e-billing, e-filling and taxpayers’awareness on taxpayers’compliance with the tax socialization as variable moderation in KPP Pratama Pekanbaru Tampan. This research data obtained from the questionnaire (primary) which is distributed to taxpayers enrolled in KPP Pratama Pekanbaru Tampan with the sampling method is random. Determination of the number of research samples with the Slovin formula and obtained a number of 100 research respondents. Research data was collected through the direct distribution of questionnaires. Furthermore, the data is processed with the test multiple linear regersi and Moderated Regression Analysis (MRA) equation with SPSS tools. The results of this research show that e-billing applications, e-filling applications, and taxpayers’ awareness have positive and significant effect on taxpayers’compliance. In addition, socialization can’t moderate taxes (weaken) the relationship of e-biling applications, e-filling applications, and taxpayers’ awareness on taxpayer compliance.